Human-centered design of complex systems: An experience-based approach. (21st June 2017) - Boy, Guy André
Abstract : This position paper presents a new approach based on my experience in the evolution of human-centered design (HCD) during four decades, and how it has struggled to become a discipline in its own right in complex socio-technical systems' creation, development and operations. The 20th century saw tremendous industrial developments based on tangible materials that were transformed and assembled to make washing machines, cars, aircraft and power plants; during its last three decades, electronics and software were incrementally added to hardware machines. Operationalization issues moved from hardware to software, making automation and user interfaces central issues. From the beginning of the 21st century, we began to do the exact opposite! Currently, we typically start a project by designing and developing technology on computers, using software only, which is later transformed into hardware (and software). I denote this shift, the 'socio-technical inversion'. Operationalization issues are moving from software to hardware, making tangibility a central issue. Three useful conceptual models are presented: the SFAC (Structure/Function versus Abstract/Concrete) model; the NAIR (Natural/Artificial versus Cognitive/Physical) model; and the AUTOS (Artifact, User, Task, Organization and Situation) pyramid. Concepts developed in this article are based on the rationalization of a long experience in the aerospace domain.